2022
DOI: 10.15403/jgld-4486
|View full text |Cite
|
Sign up to set email alerts
|

Do Patient Delay and Diagnostic Delay Influence Long Term Survival in Patients with Gastric Cancer?

Abstract: Background and Aims: Gastric cancer is one of the most common malignancies, with an aggressive evolution and a poor long-term prognosis. No screening program is available in Europe for this pathology; therefore, the delay from the appearance of the first symptom until the initiation of treatment might influence the prognosis of gastric cancer patients. We aimed to investigate the impact on the prognosis of the delay in the presentation and diagnosis in patients with gastric adenocarcinoma. Methods: Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Gastric cancer (GC) is a complex and aggressive disease that currently ranks fifth in incidence and fourth as the leading cause of cancer-related death worldwide [1]. Most cases of GC are diagnosed late, mainly due to their nonspecific symptomatology, contributing to the severity of the disease at diagnosis [2,3]. Thus, despite several advances regarding anticancer therapy in recent years, the prognosis of GC remains unsatisfactory, with a 5-year survival rate of approximately 20%, high recurrence rates, and distal metastasis events [4].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) is a complex and aggressive disease that currently ranks fifth in incidence and fourth as the leading cause of cancer-related death worldwide [1]. Most cases of GC are diagnosed late, mainly due to their nonspecific symptomatology, contributing to the severity of the disease at diagnosis [2,3]. Thus, despite several advances regarding anticancer therapy in recent years, the prognosis of GC remains unsatisfactory, with a 5-year survival rate of approximately 20%, high recurrence rates, and distal metastasis events [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that patient delays account for a large proportion of the total delay time and can have a more pronounced impact on their prognoses [13,14]. At the same time, patient delays are in uenced by patient characteristics, particularly health-seeking behaviours or beliefs [15,16].…”
Section: Introductionmentioning
confidence: 99%